Non-antipsychotic medicines and modified electroconvulsive therapy are risk factors for hospital-acquired pneumonia in schizophrenia patients - Yang, Yan; Kong, Di; Li, Qiwen; Chen, Wei; Zhao, Guocheng; Tan, Xi; Huang, Xincheng; Zhang, Zipeng; Feng, Can; Xu, Min; Wan, Ying; Yang, Mi (Frontiers in Psychiatry, 2023)
Background: Hospital-acquired pneumonia (HAP) has a significant and detrimental impact on schizophrenia patients. Non-antipsychotic medicines and modified electroconvulsive therapy (MECT) are frequently used in conjunction with antipsychotics to treat schizophrenia. Whether non-antipsychotic medicines or MECT are risk factors for HAP in schizophrenia treated with antipsychotics is still unknown. Methods: Patients with schizophrenia who were admitted to the Fourth People’s Hospital of Chengdu between January 2015 and April 2022 were included in this retrospective cohort study. Individuals with HAP were 1:1 matched to individuals without HAP (non-HAP) using propensity score matching (PSM). The risk factors for HAP were analyzed by comparing the two groups. Results: A total of 7,085 schizophrenia patients were included in this study, with a mean age of 39.77±14.45 years. 193 patients developed HAP on an average of 22.26±21.68 days after admission with an incidence of 2.73%. After 1:1 PSM, 192 patients from each group (HAP and non-HAP) were included. Multivariate logistic regression analysis showed that, combined with antipsychotics, non-antipsychotic medicines including benzodiazepines (OR =3.13, 95%CI =1.95-5.03, P＜0.001), antidepressants (OR = 3.01, 95%CI =1.22-7.44, P =0.017 ), mood stabilizers (OR =3.33,95%CI =1.79-6.20, P＜0.001), anti-parkinsonians (OR =1.97, 95%CI=1.22-3.17, P =0.005) and MECT (OR =2.58, 95%CI =1.49-4.46, P=0.001 ) were associated with a significantly increased incidence of HAP. Conclusion: The incidence of HAP in schizophrenia patients in our cohort was 2.73%. MECT and non-antipsychotic medicines, including antidepressants, mood stabilizers, benzodiazepines, and anti-Parkinson’s medications, were risk factors for HAP in schizophrenia patients treated with antipsychotics.